Momentum and nonlinear price discovery in sovereign credit risk and equity markets of the organization of Islamic cooperation (OIC) countries - Ngene, Geoffrey; M. Kabir Hassan (Penerbit Universiti Kebangsaan Malaysia, 2012)
This paper hypothesized that there is a differential response by agents to changes in sovereign credit risk in both calm (low default risk) and turbulent (high default risk) markets. These market conditions create two different states of the world or regimes. The two model regimes have been made using threshold cointegration and vector error correction model in three possible pairs of sovereign CDS, bond and equity markets for four emerging markets. Moreover, evidence of momentum in cointegration relationships in 75% of the time. Positive and negative divergences adjust to equilibrium relationship and value (threshold) at different speeds and magnitudes depending on the regime. Moreover, short-term nonlinear adjustment process is found in 50% of possible asymmetries. The informativeness of each asset in a pair is nonlinear and regime dependent in 14/24 possible price discovery processes. Therefore, dynamic interaction among assets held in a portfolio shift with regime change. Investors, in making decisions regarding portfolio rebalancing and hedging against downside risk need to identify when regimes change to make informed decisions while policy makers need to identify the threshold below or above which policy intervention in the market becomes necessary. Linear modeling may provide mis-specified and biased results as indicated by comparative results of linear and nonlinear modeling.